Treatment concerns for bullous pemphigoid in the COVID‐19 pandemic era. Issue 6 (25th July 2020) - Azimi, Seyyede Zeinab; Firooz, Alireza; Murrell, Dedee F.; Daneshpazhooh, Maryam
Abstract: Bullous pemphigoid (BP) is the most common autoimmune blistering disease with subepidermal involvement, typically affecting the elderly. It has spontaneous remissions and exacerbations with significant morbidity. A novel coronavirus called severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) is responsible for the new universal coronavirus disease 2019 (COVID‐19) pandemic. The pandemic made concerns, especially about immunosuppressive therapy. In this article, we reviewed the management of BP in the COVID‐19 pandemic era. The data about the best management of autoimmune bullous diseases like BP, during the outbreak of COVID‐19, are evolving and updated every day.